Increased amounts of laminin in GCF from untreated patients with periodontitis - Figueredo, C. M. S.; Gustafsson, A. (Journal of clinical periodontology, 2000)
Background/aims: Our aim was to compare the levels of laminin and interleukin‐8 (IL‐8) in GCF from inflamed shallow (GP) and deep pockets (PP) in patients with periodontitis to these levels in GCF from inflamed shallow pockets (GG) in subjects with gingivitis alone. Method: Lactoferrin was used as a marker for the number of neutrophils in the sites sampled. The periodontitis group consisted of 13 subjects, having at least 6 sites with a pocket depth 5 mm. The healthy control group consisted of 12 subjects with no clinical signs of periodontal destruction. GCF was collected with paper strips and the volume was measured immediately after sampling. Laminin, lactoferrin and IL‐8 were measured using specific antibodies with an ELISA. Results: The total amount of laminin was significantly higher in PP than in GG, but no significant difference was seen between GP and PP. The concentration and the total amounts of lactoferrin were similar in the three groups. The ratio between laminin and lactoferrin was higher in the samples from the patient, suggesting that neutrophils in patients are more activated and degrades more of the membrane per cell. The total amounts of IL‐8 were very similar in the 3 groups, while the concentration also tended to be higher in the GP. Conclusions: Our study showed higher amounts of laminin in GCF from patients with periodontitis suggesting the presence of hyperactive neutrophils during the transmigration process through the endothelium/epithelium.